Technical Agroclimatic Committees (MTA): A detailed guide for implementing MTA, step-by-step - Giraldo Mendez, Diana Carolina; Martínez Barón, Deissy; Loboguerrero Rodriguez, Ana María; Gumucio, Tatiana; Martínez, Jesús David; Ramírez Villegas, Julián Armando (2019)
The Local Technical Agroclimatic Committees (LTACs) are process of dialogue between a diversity of local actors, that include researchers, techniques, representatives of the public and private sector and farmers that seek to understand the possible climate behavior in a territory and the recommendations to reduce the risks associated with the expected climate variability (Loboguerrero et al. at 2018). As a result of this dialogue, an a agroclimatic bulletin is published with the weather forecast, its possible impact on crops with specific conditions of time and space, associated to recommendations for decision making for every productive system. Weather forecasts, are generated in consensus with the meteorological services of each country and with the existing agro-meteorology groups of different institutions, in order to identify the best practices for adaptation to climatic phenomena, which are transferred to local technicians and producers through the Local Agroclimatic Bulletin. During the last five year, we have achieved that 197 institutions in Honduras, Colombia, Guatemala, Nicaragua and Chile adopt the approach of LTACs, as a mechanism to reduce agroclimatic risks. This manual provides step-by-step instructions for working the LTACs approach. It is aimed mainly at leading institutions in the agricultural sector that have an interest in implementing a discussion space in their region. This approach consists of seven steps, which are carried out with the participating institutions. Given the specific nature by location, there is a series of preparatory activities that need to be done before each meeting.